Trust, Testimony, and the Epistemic Value of Historical Narrative - Tozzi, María Verónica (2025)
A significant contribution of narrativist philosophy of history (whether analytical, phenomenological, or poststructuralist) lies in its critique of relying solely on "strictly" epistemic criteria to evaluate historical narratives. Rather than assessing them based on empirical evidence alone, which is often seen as neutral and value-free, narrativism calls for a broader perspective. This is because no description of people and their behavior can be value-neutral. Narrativism thus aligns with constructivist theories of linguistic meaning, linked to the "linguistic turn." I propose a dialogue between narrativism and the epistemology of testimony. By adopting the latter's concepts (trust, authority, and epistemic community), narrativism can 1) reconstruct practices of epistemic validation in history and 2) address the historian’s responsibility to marginalized voices. Simultaneously, I argue that the epistemology of testimony should engage with narrativism to better understand the complexity of narrative constructions in epistemic communities.